Delayed presentation of Subclavian venous thrombosis following undisplaced clavicle fracture. - Kochhar, T; Jayadev, C; Smith, J; Griffiths, E; Seehra, K (2008)
Medial clavicle fractures are uncommon, accounting for approximately 5 percent of all clavicle fractures. Vascular injuries are uncommon but are recognised as either an immediate complication due to transection of the vessel by the displaced fracture, or as a late complication, secondary to compression from abundant callus formation. We present an unusual case of positional venous insufficiency in the upper limb as an immediate complication of a closed, minimally displaced clavicle fracture, with secondary subclavian venous thrombosis formation eleven days following the injury.